Successful therapy of vulvodynia with local anesthetics: a case report - Weinschenk, Stefan; Brocker, Kerstin A.; Hotz, Lorenz; Strowitzki, Thomas; Joos, Stefanie (Forschende Komplementärmedizin, 2013)
Background: Vulvodynia often occurs with unexplained vulvar pain and hyperesthesia, sexual dysfunction, and psychological disability, lacking an organic or microbiological substrate. Case Report: A 25-year-old woman with generalized, unprovoked vulvodynia for 12 years was treated repeatedly with procaine 1% for 14 sessions after she had previously had numerous unsatisfying multidisciplinary treatments. We observed a decrease in pain scores on the visual analogue scale (VAS) from initially 8-9 to presently 0-2. Injection sites were: Head's zones and trigger points of the lower abdomen, regional hypogastric ganglia, bilateral maxillary sinus, and scars of the lower jaw. No major adverse events were observed. Injections to remote sites improved symptoms more strongly than local or regional therapy. After a 3-year follow-up the patient is free of symptoms. Conclusion: Therapy with local anesthetics (TLA, neural therapy) can be a useful additional therapy in complicated cases of vulvodynia. Further studies on the underlying mechanism of injections into remote foci (interference field, stoerfeld) and the effectiveness of TLA in chronic pain syndromes should be performed.